Gastrin: From Physiology to Gastrointestinal Malignancies. Issue 1 (26th November 2021) - Duan, Suzann; Rico, Karen; Merchant, Juanita L
Abstract: Abetted by widespread usage of acid-suppressing proton pump inhibitors (PPIs), the mitogenic actions of the peptide hormone gastrin are being revisited as a recurring theme in various gastrointestinal (GI) malignancies. While pathological gastrin levels are intricately linked to hyperplasia of enterochromaffin-like cells leading to carcinoid development, the signaling effects exerted by gastrin on distinct cell types of the gastric mucosa are more nuanced. Indeed, mounting evidence suggests dichotomous roles for gastrin in both promoting and suppressing tumorigenesis. Here, we review the major upstream mediators of gastrin gene regulation, including inflammation secondary to Helicobacter pylori infection and the use of PPIs. We further explore the molecular biology of gastrin in GI malignancies, with particular emphasis on the regulation of gastrin in neuroendocrine neoplasms. Finally, we highlight tissue-specific transcriptional targets as an avenue for targetable therapeutics.